Edukasi Peningkatan Penjualan Lewat Pemasaran Online Kepada Siswa SMA Negeri 09 Kota Bengkulu - Gagasadewa, Putra; Susena, Karona Cahya (Universitas Dehasen Bengkulu, 2024)
The community service carried out aims to evaluate the effectiveness of online marketing training in increasing sales, especially among students at SMA Negeri 09 Bengkulu City. This training method is designed to increase their understanding of digital marketing strategies and best practices in achieving sales targets. The research was carried out by collecting data before and after training to assess the increase in students' knowledge and skills in implementing online marketing strategies. It is hoped that the results of this research can provide guidance for educational institutions and industry players to increase the effectiveness of digital marketing education in high schools.